2013
DOI: 10.1016/j.cgh.2013.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Type, Rather Than Number, of Mental and Physical Comorbidities Increases the Severity of Symptoms in Patients With Irritable Bowel Syndrome

Abstract: BACKGROUND Irritable bowel syndrome (IBS) has significant mental and physical comorbidities. However, little is known about the day-to-day burden these comorbidities place on quality of life (QOL), physical and mental function, distress, and symptoms of patients. METHODS We collected cross sectional data from 175 patients with IBS, diagnosed based on Rome III criteria (median age, 41 y; 78% women), referred to 2 specialty care clinics. Patients completed psychiatric interviews, a physical comorbidity checkli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
99
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(116 citation statements)
references
References 76 publications
(81 reference statements)
11
99
1
5
Order By: Relevance
“…IBS affects 15%-23% of the general population and is the most common reason for patients and generalists to consult gastroenterologists In addition, our data showed that the percentage of IBS diagnosis and PH is in accordance with other studies. IBS affects 15%-23% of the general population and is the most common reason for patients and general practitioners to consult gastroenterologists (6,20,26,29,31,39,42) . Globally, the percentage of adult population with an active headache disorder is 47%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…IBS affects 15%-23% of the general population and is the most common reason for patients and generalists to consult gastroenterologists In addition, our data showed that the percentage of IBS diagnosis and PH is in accordance with other studies. IBS affects 15%-23% of the general population and is the most common reason for patients and general practitioners to consult gastroenterologists (6,20,26,29,31,39,42) . Globally, the percentage of adult population with an active headache disorder is 47%.…”
Section: Discussionmentioning
confidence: 99%
“…However, IBS is also often accompanied by another extra-intestinal symptoms, as asthma and cerebral pain symptoms as primary headache. The pathophysiology mechanisms suggest that IBS patients with one or more somatic comorbitdities might represent a separate sub-group (6,17,20,29,39,42) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anxiety is the most common psychological complaint among patients with severe IBS 37 . Anxiety can increase attention to somatic symptoms, lead to more frequent health-care utilization, and impact family and social relationships.…”
Section: Psychosocial Factors Anxietymentioning
confidence: 99%